Literature Review: the Effect of Diaphragmatic Breathing Exercise on Ashtma - Rini Widarti; Sevy Astriyana; Fatchurrohmah Ines Prabandari (Indonesian Journal of Global Health Research, 2025)
Asthma is a disease that affects the respiratory tract in the lungs and is characterized by shortness of breath, coughing, and wheezing. An asthma treatment usually uses drugs and identifies asthma triggers. Breathing exercises are non-pharmacological therapies to overcome asthma symptoms. Diaphragmatic breathing is useful in carrying out effective breathing during an asthma attack so that sufferers do not get tired easily. This study aims to determine the effect of diaphragmatic breathing exercise (DBE) on asthma symptoms. This study uses a literature review design on electronic data-based Google Scholar, Pubmed, and ScienceDirect. 5 articles were found that met the inclusion and exclusion criteria. 1 article comparing the effect of DBE with Nostril Breathing Exercise on shortness of breath and fatigue due to asthma, one article comparing the effectiveness of DBE and Buyteko Breathing Technique (BBT) on asthma control and vital lung function. Three articles discuss the effect of DBE on decreasing respiratory rate, increasing oxygen saturation, and increasing PEFR. The management of DBT in asthma patients has an effect on asthma symptoms by reducing the workload of breathing, reducing respiratory rate and shortness of breath, increasing oxygen saturation, and improving lung respiratory function.